Explant of aortic stent grafts following endovascular aneurysm repair. (October 2019) - Boyle, E; McHugh, SM; Elmallah, A; Lynch, M; McGuire, D; Ahmed, Z; Canning, C; Colgan, MP; O'Neill, SM; O'Callaghan, A; Martin, Z; Madhavan, P
Background: Failure of endovascular aneurysm repair may require explant of the stent graft in a subset of patients. We sought to assess outcomes in a cohort of patients undergoing explant of endovascular aneurysm repair in both emergency and elective settings. Methods: Patients undergoing explant of endovascular aneurysm repair were identified from a prospectively maintained database, with additional information obtained through retrospective analysis of medical records. Results: Over a 21-year period, 1997–2018 (May), there were 597 endovascular aneurysm repair procedures performed in our institution for abdominal aortic aneurysm. There were 19 endovascular aneurysm repair explants; five of these were referrals from other vascular centres. The median age was 73 years (range 46–81). The median length of time from insertion to explant was 39.2 months (range 0–153). Indications for elective explant were type Ia endoleak (n = 4), type 1b endoleak (n = 1), type II endoleak with increasing sac size (n = 1), type I/III endoleak (n = 1), type IV endoleak (n = 1), and increasing sac size without evident endoleak (type V, n = 2). The remaining nine cases were emergency procedures, with four patients presenting with rupture post endovascular aneurysm repair, four patients presenting with acute stent thrombosis, of which one also had a type 1a endoleak and one aorto-enteric fistula. There were no mortalities in the elective group and three mortalities in the emergency group (0 vs 33.3%, p  = 0.087). Overall 30-day mortality was 15.8% Conclusion: Explant of aortic stent grafts can be associated with high mortality and morbidity rates, especially in the emergent setting. Patient and device selection and post-operative surveillance remain vitally important to optimise outcomes post endovascular aneurysm repair.